Is Psychological Well-being still exist? Descriptive Study at College-Students Athlete - Candra, Adiska Rani Ditya; Karjadi, Moch Senoadji; Sobihin, Sobihin; Romadhoni, Wiga Nurlatifa; Wicaksono, Anggit; Nafa, Septiana Azizatun; Afif, Dwanda Sangga Hidayat; Putriani, Anisa Sabhrina (Universitas Negeri Semarang, 2023)
Post-covid recovery, there is a policy in regulating new activities, by reducing limitations in movement and starting to normalize activities without reducing and ignoring health protocols. One of the educational activities is starting to be active in entering the Offline or offline environment. The start of active activities in the college environment is followed by active student activities in active participation in extra activities in improving and developing interests and talents. The problem faced is, do students who were previously active in Students Club (UKM) activities still have the motivation in achieving. What are your opinions, and views on participating and achieving in this activity? This study aims to measure the psychological well-being experienced by students who are also athletes. The measurement was carried out on UKM Sports athletes. Measurement using the psychological well-being scale (PSWB). Data analysis uses a descriptive percentage. The results of this study revealed that the psychological well-being of athletes was very high only 13.79%, for the high category it was 28.97%, for the sufficient category it was 26.90%, the other results in the low and very low categories were 22,07% and 8.28%. UKM athletes must come back with enough motivation to continue their careers to get sports achievements. Apart from that, support from various parties is really needed is psychological well-being which should be available and present in order to ensure a sense of security, comfort, and the creation of a passion for recovery of fighting power after online activities carried out so far